DIABETIC ENCEPHALOPATHY: A HISTOPATHOLOGICAL UPDATE - Volos, Liliya; Mykhaylichenko, Tetyana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES We aimed to examine small vessels in the brain for histological changes in patients with type 2 diabetes mellitus and diabetic encephalopathy. METHODOLOGY We studied the histopathological changes in the brain in 17 autopsy cases. The microscope slides were stained with Hematoxylin and Eosin, Nissl and Bielschowsky methods and PAS-reaction. RESULTS The high density of the capillary network, especially in the cortex of the frontal and temporal areas, together with segmental spasm and an expansion of the perivascular space of Robben-Virchow were observed. The early changes in the capillary wall were determined not only by the thickening of the basement membrane with the accumulation of PAS-positive substances but also by its cleavage with the proliferation of endothelial cells. Late manifestations of vessel changes include capillary fibrosis, characterized by the presence of argentophilic reticulin and collagen fibers and proliferation of pericytes in the capillary wall. Thin-walled microaneurysms, early morphological manifestations of diabetic encephalopathy, were also seen. Segmental fibrinoid necrosis with the formation of miliary dissecting aneurysms and parietal and obstructive thrombi were seen in areas of ischemic necrosis of brain tissue in the cortical cerebral arteries. Neurodystrophic changes in neurons, loss of small-cell perivascular spongiosis and plaque formation were quite pronounced. The most obvious changes were in the upper layers of the cortex where focal atrophy was more prominent than laminar. A large number of corpora amylacea can be significant not only in the foci of necrosis but also in areas of chronic ischemia. CONCLUSION Cerebral microangiopathy is a morphological sign of diabetic encephalopathy.